1999
DOI: 10.1046/j.1365-2710.1999.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related differences in pharmacokinetics and their clinical significance

Abstract: SUMMARYmay involve differences in physical constitution (body water space, muscle mass, organ blood flow and organ In this review I have attempted to summarize gender function) and physiology (menopause, pregnancy and differences in pharmacokinetics involving the cytomenstruation) between women and men. In addition, chrome P450 (CYP) isozymes of young and mature as hormonal steroid contraceptives are used by some adults, excluding the effects of the menstrual cycle, women, therapeutic drugs for use by pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
169
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(180 citation statements)
references
References 86 publications
7
169
1
3
Order By: Relevance
“…Sex‐related pharmacokinetic disparities have been reported for other drugs. There are many potential reasons for sex differences in CC‐292 pharmacokinetics, such as differences in gastric pH, which is higher in females, lower hepatic blood flow and consequently lower hepatic metabolic capacity,22, 23 which could partly explain the findings. However, the resulting differences in drug exposures between female and male subjects were small (below 26%) relative to the observed overall variability in the pharmacokinetics of CC‐292.…”
Section: Discussionmentioning
confidence: 95%
“…Sex‐related pharmacokinetic disparities have been reported for other drugs. There are many potential reasons for sex differences in CC‐292 pharmacokinetics, such as differences in gastric pH, which is higher in females, lower hepatic blood flow and consequently lower hepatic metabolic capacity,22, 23 which could partly explain the findings. However, the resulting differences in drug exposures between female and male subjects were small (below 26%) relative to the observed overall variability in the pharmacokinetics of CC‐292.…”
Section: Discussionmentioning
confidence: 95%
“…Many studies have mapped out the molecular biology of this superfamily and nowadays it can be divided into many subfamilies, each of which (particularly those belonging to numbers 1 to 4) is linked to a different set of drugs [33,56]; moreover, numerous investigators have identified the substrate specificities of each single isoform [33]. Recently, some studies which report the metabolism of substrates as models for specific enzymatic pathways in liver preparations of farm animals have been published too [29,37,49,55].…”
Section: Discussionmentioning
confidence: 99%
“…liver, intestine), wide substrate spectrum, susceptibility to drug interactions as well as interindividual variable expression levels [3,12,31,56].…”
Section: Discussionmentioning
confidence: 99%
“…Identifying these sexually dimorphic mouse Cyp2c enzymes in liver may aid in understanding differences in drug potency observed in male versus female mice. However, sexual dimorphism is much less pronounced in human models in comparison with rodent models (Lofgren et al, 2008;Tanaka, 1999), which must be taken into account when using the mouse as a model for human disease and drug metabolism.…”
Section: Discussionmentioning
confidence: 99%